Faecal Microbiota Transplantation as an Adjuvant Treatment for Extraintestinal Disorders: Translating Insights from Human Medicine to Veterinary Practice - Alice Nishigaki; Julian R. Marchesi; Renato L. Previdelli (Veterinary Sciences)
Faecal microbiota transplantation (FMT) has emerged as a transformative therapy in human medicine, particularly for managing recurrent Clostridioides difficile infections and other gastrointestinal (GI) disorders. Beyond the GI tract, FMT has shown potential in addressing extraintestinal conditions in people, including metabolic, immune-mediated, dermatological, neurological, and infectious diseases. Research in people has highlighted its efficacy in decolonising multidrug-resistant organisms in infection, mitigating autoimmune diseases, and improving outcomes in metabolic disorders such as obesity and diabetes. Furthermore, FMT has also been linked to enhanced responses to immunotherapy in cancer and improved management of hepatic and renal conditions. These findings underscore the intricate connections between the gut microbiome and systemic health, opening novel therapeutic avenues. In veterinary medicine, while FMT has demonstrated benefits for GI disorders, its application in extraintestinal diseases remains largely unexplored. Emerging evidence suggests that conditions such as atopic dermatitis, chronic kidney disease, immune-mediated diseases, and behavioural disorders in companion animals could benefit from microbiome-targeted therapies. However, significant gaps in knowledge persist, particularly regarding the long-term safety and efficacy for veterinary applications. This review synthesises findings from human medicine to assess their relevance for veterinary applications and future research.